Double Barrel Nasal Trumpets to Prevent Upper Airway Obstruction after Nasal and Non-Nasal Surgery - Macario Camacho; Justin M. Wei; Lauren K. Reckley; Sungjin A. Song (Anesthesiology Research and Practice)
Objectives. During anesthesia emergence, patients are extubated and the upper airway can become vulnerable to obstruction. Nasal trumpets can help prevent obstruction. However, we have found no manuscript describing how to place nasal trumpets after nasal surgery (septoplasties or septorhinoplasties), likely because (1) the lack of space with nasal splints in place and (2) surgeons may fear that removing the trumpets could displace the splints. The objective of this manuscript is to describe how to place nasal trumpets even with nasal splints in place. Materials and Methods. The authors describe techniques (Double Barrel Technique and Modified Double Barrel Technique) that were developed over three years ago and have been used in patients with obstructive sleep apnea (OSA) and other patients who had collapsible or narrow upper airways (i.e., morbidly obese patients). Results. The technique described in the manuscript provides a method for placing one long and one short nasal trumpet in a manner that helps prevent postoperative upper airway obstruction. The modified version describes a method for placing nasal trumpets even when there are nasal splints in place. Over one-hundred patients have had nasal trumpets placed without postoperative oxygen desaturations. Conclusions. The Double Barrel Technique allows for a safe emergence from anesthesia in patients predisposed to upper airway obstruction (such as in obstructive sleep apnea and morbidly obese patients). To our knowledge, the Modified Double Barrel Technique is the first description for the use of nasal trumpets in patients who had nasal surgery and who have nasal splints in place.